States' Use Of Medicaid Managed Care 'In Lieu Of Services' Authority To Address Poor Nutrition - Garfield, Kathryn; Hanson, Erika; Shachar, Carmel; Stain, Pascale; Mozaffarian, Dariush (Health affairs (Millwood, Va.), 2025)
In response to rising health, economic, and equity burdens of suboptimal nutrition, health care stakeholders are increasingly integrating nutritional supports into health care delivery and financing. In January 2023, federal guidance clarified that states may use "in lieu of services and settings" (ILOS) authority to address health-related social needs, including nutrition, in Medicaid managed care. However, few data are available regarding ILOS implementation. This analysis reviewed ILOS policies based on managed care documents from forty states as of October 1, 2024. Thirty-five states have authorized ILOS to address behavioral health, and fourteen states have authorized ILOS to address general medical needs. Twelve states use ILOS to address health-related social needs; of these, only ten address nutrition. In addition, fewer than half of the forty states provide robust guidance regarding evaluation or establishment of new ILOSs. We examine the policy implications of these findings and provide recommendations to strengthen the role of ILOS in improving nutrition, health care costs, and health equity.